Remittances and the Real Exchange Rate - Lopez, Humberto (World Bank, Washington, DC, 2012)
Existing empirical evidence indicates that remittances have a positive impact on a good number of development indicators of recipient countries. Yet when flows are too large relative to the size of the recipient economies, as those observed in a number of Latin American countries, they may also bring a number of undesired problems. Among those probably the most feared in this context is the Dutch Disease. This paper explores the empirical evidence regarding the impact of remittances on the real exchange rate. The findings suggest that remittances indeed appear to lead to a significant real exchange rate appreciation. The paper also explores policy options that may somewhat offset the observed effect.